Konsep Integrasi Nilai-Nilai Pendidikan Agama Islam Dalam Proses Belajar Mengajar - Rudianto, Rahmat; Mahfud, Muhammad (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
The current picture of education in Indonesia seems to have drawn a lot of criticism from various circles of society because it is considered not fully capable of making students have moral values that are embodied in student behavior. Not only in personal and social life, deviant behavior is also seen in the religious behavior of adolescents today. This study refers to written materials related to the discussion of the concept of integrating the values of Islamic religious education in the teaching and learning process. This research includes library research. The data extracted in this study are about the integration of the values of Islamic religious education in the learning process, which are contained in books on the philosophy of Islamic education; second, secondary data, in the form of a theoretical review on the integration of the values of Islamic religious education in the learning process either in the form of articles in magazines, journals, newspapers related to the discussion. The data collection process was carried out using documentation techniques. This technique is used by researchers to explore data relating to the study of philosophy about the integration of the values of Islamic religious education. Meanwhile, data analysis was carried out using content analysis techniques, which researchers used with the aim of finding, identifying, processing and analyzing. The results of the research show that the integration of the values of Islamic religious education in the teaching and learning process is carried out from the planning stage (preparation of lesson plans), the implementation of learning, to the evaluation of learning.